Inovasi produk camilan lokal: studi kewirausahaan pada usaha keripik kaca sebagai peluang bisnis kreatif - Effendy, Syazani Azmy (Maliki Interdisciplinary Journal, 2026)
sted to the tastes of young people. This study aims to see how big the market opportunity for glass chips is among students, and to formulate the right marketing strategy so that this product can develop. The writing was carried out using a qualitative descriptive method by observing student consumption habits, the campus environment, and snack business trends. From the results of the study, it was found that students are a very potential target market because they like to snack and are open to new products. Marketing strategies that can be applied include active promotion through social media, an early booking system (pre-order), savings packages, cooperation with campus organizations, attractive packaging appearance, delivery services in the campus area, and loyalty programs such as purchase bonuses. If all of this potential is managed well and combined with the right strategy, the glass chips business has a great opportunity to develop and be widely known in the student environment.